REVIEW OF PULMONARY EMBOLISM - K. GAYATHRI DEVI; G. VAMSI KRISHNA MURTHY (International Journal of Pharma and Bio Sciences, 2012)
Pulmonary embolism is a blockage of main artery or one of its branches of lung by the fat, amniotic fluid, embolisation of air or any other foreign substances. It is also due to formation of thrombus [blood clot] in the arteries of lung. Due to the pulmonary embolism the blood circulation in the body will be effected. Sometimes PE leads to death also by the lacking of breathing. In USA the annual incidence rates per 1000 persons aged 65-69 are 1.3 affected by pulmonary embolism. The diagnosis of pulmonary embolism at the earlier stage will be difficult because the symptoms like difficulty in breathing and chest pain are not easily differentiated from the other diseases like myocardial infarction. The usage of drugs like anti coagulants and thrombolytic cause bleeding problems even though they shows the antagonistic activity of pulmonary embolism at higher doses. Physician responsibility is to successfully avoid bleeding disorders are at the time of prevention of pulmonary embolism. And also by conducting of programs which should strive to coordinate care , by region wide guidelines and by implementing of care programs there is a chance to elaborate knowledge about the pulmonary embolism to the physicians and also there is a chance to bring awareness among the public which may decreases the number deaths due to pulmonary embolism annually.